2020
DOI: 10.1111/jfpp.14853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and optimization of microwave‐assisted extraction of bioactive compounds from eggplant peel by‐product

Abstract: Plant by-products processing industries are rich and inexpensive sources of valuable bioactive compounds, including polyphenols, carotenoids, flavonoids, anthocyanins, and vitamins. The nonedible portions constitute 25%-30% of plant by-products. The term "by-product" means reusable wastes with a good market value. In the processing of fruits and vegetables, such wastes are mainly peels, seeds, skins, leaves, unusable pulp, and stems. In addition to dealing with pollution problems, they can be sources of valuab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 49 publications
7
36
0
Order By: Relevance
“…The observed increment in the yield of solasodine with increase in mass can be attributed to the increased mass transfer of metabolites from the plant matrix to the solvent when larger weights of the plant material were used. This observation is in agreement with what was reported by Doulabi et al (2020).…”
Section: Resultssupporting
confidence: 94%
“…The observed increment in the yield of solasodine with increase in mass can be attributed to the increased mass transfer of metabolites from the plant matrix to the solvent when larger weights of the plant material were used. This observation is in agreement with what was reported by Doulabi et al (2020).…”
Section: Resultssupporting
confidence: 94%
“…Other agri-food by-products have been exploited for anthocyanin extraction, such as black carrot pomace [ 39 ], eggplant by-product [ 40 , 41 ], black soybean seed coat [ 42 ], purple corn cob and corn husk [ 43 ], onion peel [ 44 ], black rice bran [ 45 ], and some berry by-products (e.g., blueberry [ 46 ], red raspberry [ 47 ], sweet cherry [ 48 ], sour cherry [ 49 ], bilberry [ 50 ], blackcurrant [ 51 ], blackberry [ 52 ], jabuticaba [ 53 ], black chokeberry [ 54 ], and mulberry [ 55 ], among others). Nonetheless, they are less explored and less known when compared to grape pomace.…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Indeed, several studies conducted with MW have shown an increase in anthocyanin extraction from agri-food by-products as these parameters are intensified. When evaluating the MW treatment effect on eggplant peel, Doulabi et al [ 40 ] reported that the anthocyanin extraction enhances as the microwave power increases (100–300 W). Şahin et al [ 49 ] verified that anthocyanin recovery from sour cherry peels gradually enhanced as the microwave power (350–500 W) and irradiation time (0.5–1.5 min) increased.…”
Section: Innovative Processes For Anthocyanin Extraction From Agri-food By-productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing new extraction techniques for food and pharmaceutical industries has increasingly attracted considerable interest because of safety concerns, the demand for minimizing the energy costs, environmental restrictions, and public health regulations (Carvalho et al, 2005;Chen et al, 2020;Doulabi et al, 2020).…”
mentioning
confidence: 99%